Driving force analysis and multi-scenario simulation of landscape ecological risk in the Jianghan Plain, China - Heng Liu; Lu Zhou; Diwei Tang (Scientific Reports)
Abstract As a key food production base, land use changes in the Jianghan Plain (JHP) significantly affect the surface landscape structure and ecological risks, posing challenges to food security. Assessing the ecological risk of the JHP, identifying its drivers, and predicting the risk trends under different scenarios can provide strategic support for ecological risk management and safeguarding food security in the JHP. In this study, the landscape ecological risk (LER) index was constructed by integrating landscape indices from 2000 to 2020, firstly analyzing its spatiotemporal characteristics, subsequently identifying the key influencing factors by using the GeoDetector model, and finally, simulating the risk changes under the four scenarios by using the Markov-PLUS model. The results showed that: (1) Cropland was the dominant land use, and the most significant decreases and increases occurred in cropland and built-up land, respectively. The primary land use conversion was cropland to built-up land and the interconversion of cropland and water body. (2) LER exhibited a trend of initially increasing and subsequently decreasing, and the risk levels were predominantly medium and higher. The spatial pattern was high in the southeast and low in the central and northern areas. (3) The spatiotemporal patterns of LER resulted from the combined effect of multiple factors and were mainly influenced by the natural environment, of which the NDVI was the first dominant factor. (4) The land use intensity was higher in the natural and economic development scenarios than in the cropland and ecological protection scenarios, and the predicted LER in 2030 was higher in the former than in the latter two. These findings are important for formulating scientific and reasonable land use planning and ecological risk management strategies to balance economic growth and ecological preservation and maintain food security and ecological sustainability in the JHP.